Does sewage sludge amendment to soil enhance the development of Silver birch and Scots pine? - Vaitkutė, Dovilė; Baltrėnaitė, Edita; Booth, Colin A; Fullen, Michael A (Hungarian Geographical Bulletin, 2010)
Sewage sludge can be used to improve forestry soil properties, because it is rich in phosphorus, nitrogen and organic material and, thus, can enhance the growth of tree seedlings in poor quality soils. Our study was performed on a site amended with industrial sewage sludge and aff orested with birch and pine seedlings. To evaluate the growth of tree seedlings, tree dry biomass, height, diameter, root/shoot ratio, specific root length, shoot and root length were calculated. Higher concentrations of heavy metals and no significant increase in the biomass of trees on sewage sludge amended soil suggest an inhibitory effect of heavy metals on tree biomass growth.The site treated with sewage sludge had signifi cantly higher soil moisture content, soil pH, total copper and total lead concentrations and significantly lower exchangeable acidity. Tree tissues at the sewage sludge treated site contain significantly higher concentrations of copper and cadmium. Therefore, both positive and negative impacts of treatment are apparent. In terms of management strategies, it is recommended that the chemical quality of sewage sludge is analyzed prior to possible field applications and only sewage sludges with toxic heavy metal concentrations below accepted safety limits are applied.